Beyond Formal Validity: Substantive Consent and the Annulment of Coerced Marriage in the Indonesian Religious Courts - Muhammad Ibnu Tohir; Hamdan Arief Hanif; Muhammad Iman Kurniawan; Arga Aditya Firmansyah (PFL: Plural Family Law Review, 2026)
Free consent is the substantive, not merely formal, foundation of a valid marriage under Indonesian Islamic family law a proposition this article advances through doctrinal analysis of South Jakarta Religious Court Decision Number 100/Pdt.G/2023/PA.JS, in which a marriage contracted under parental coercion was annulled. Using a normative-qualitative case-study approach that combines statutory, KHI, and classical fiqh analysis with close reading of the certified court decision, the study identifies two principal findings. First, the petitioner, a woman who had never met the respondent prior to the akad, sought annulment on the ground that the marriage was orchestrated entirely by the parents of both parties without her genuine consent, and that the respondent left for Surabaya the day after the ceremony without consummation. Second, the panel grounded annulment on Article 6(1) and Article 22 of Law No. 1/1974, Article 71(f) of the Compilation of Islamic Law, and prophetic traditions affirming a woman’s right to repudiate a marriage contracted without her permission. The article argues that these sources converge on a four-register theory of marital consent as rukn of contract, statutory condition, codified Islamic law, and treaty-based right and offers an evidentiary template that practitioners may apply to distinguish genuine coercion from post-hoc dissatisfaction.